A public policy perspective of the Dark Web. Issue 1 (2nd January 2017) - Chertoff, Michael
ABSTRACT: The Dark Web is at the centre of the debate over whether online anonymity should be maintained in spite of the illegal activity that it enables. Policy-makers must gain an understanding of the Dark Web in order to engage intelligently in the debate and enact effective Dark Web policy. This paper aims to provide context and policy recommendations pertaining to the Dark Web based on open-source research. The Dark Web's complete history, from its creation to the latest incidents of government intervention, remains relevant to today's debate. By examining cases where a government agency has enforced laws on the Dark Web, one can glean an understanding of which policies will be most successful going forward. This paper explores two specific policy topics: (1) determining the appropriate role of government in regulating the Dark Web and (2) exploring the most effective and reasonable methods for government to intervene. As the United States develops and refines policy regarding the Dark Web, the international community will also be manoeuvring to put in place regulations, and it is essential that these regulations be compatible while staying true to the values of the internet users that those governments serve.